Evaluation of trophic transfer in the microbial food web during sludge degradation based on 13C and 15N natural abundance. (1st December 2018) - Onodera, Takashi; Kanaya, Gen; Hatamoto, Masashi; Kohzu, Ayato; Iguchi, Akinori; Takimoto, Yuya; Yamaguchi, Takashi; Mizuochi, Motoyuki; Syutsubo, Kazuaki
Abstract: Carbon and nitrogen stable isotope ratios (δ 13 C and δ 15 N) were determined in activated sludge, which was exposed to endogenous conditions for 36 days and contained a wide diversity of organisms across several trophic levels. The aim of this study was to elucidate the fluctuation of δ 13 C and δ 15 N through trophic transfer in the microbial consortia. The sludge was evaluated in view of sludge mass, bacterial community, higher trophic organisms, sludge δ 13 C and δ 15 N, and δ 15 N and δ 18 O of nitrate. The results show that the activated sludge became more enriched with 15 N as degradation proceeded. Eventually, the mixed liquor volatile suspended solid concentrations in the activated sludge decreased from 1610 to 710 mg/L and the δ 15 N of the sludge increased from 8.3‰ to 10.8‰. In contrast, the δ 13 C values of the sludge were stable. Microscope observations confirmed that consumers such as Rotifera, Tardigrada and Annelida ( Aelosoma sp.) were present in the activated sludge for the entire operational period. The abundance of those organisms drastically changed during the operational periods, and the diversity in bacterial community also changed, resulting in community succession. Changes in biotic community, reduction in sludge mass, and increase in δ 15 N of the sludge occurred during the sludge degradation processes. This implies that the sludge degradation was partly caused by the trophic conversion of the sludge-derived nitrogen in the food web. The δ 15 N of the sludge can be used as an indicator of the sludge degradation through trophic transfer in wastewater treatment reactors. These findings provide new insights into understanding trophic transfer during microbial community succession and the effects of the feeding process on sludge degradation. Graphical abstract: Highlights: Stable isotope ratios (δ 13 C, δ 15 N, δ 18 O) were measured in activated sludge (AS). δ 15 N was applied to determine the predation processes of the food web in AS. δ 15 N increased and δ 13 C was nearly constant under degradation of AS. Biotic community including bacteria, protozoa, and metazoa varied under degradation.